Art on the Nanoscale and Beyond. Issue 9 (15th December 2015) - Yetisen, Ali K.; Coskun, Ahmet F.; England, Grant; Cho, Sangyeon; Butt, Haider; Hurwitz, Jonty; Kolle, Mathias; Khademhosseini, Ali; Hart, A. John; Folch, Albert; Yun, Seok Hyun
Abstract : Methods of forming and patterning materials at the nano‐ and microscales are finding increased use as a medium of artistic expression, and as a vehicle for communicating scientific advances to a broader audience. While sharing many attributes of other art forms, miniaturized art enables the direct engagement of sensory aspects such as sight and touch for materials and structures that are otherwise invisible to the eye. The historical uses of nano‐/microscale materials and imaging techniques in arts and sciences are presented. The motivations to create artwork at small scales are discussed, and representations in scientific literature and exhibitions are explored. Examples are presented using semiconductors, microfluidics, and nanomaterials as the artistic media; these utilized techniques including micromachining, focused ion beam milling, two‐photon polymerization, and bottom‐up nanostructure growth. Finally, the technological factors that limit the implementation of artwork at miniature scales are identified, and potential future directions are discussed. As research marches toward even smaller length scales, innovative and engaging visualizations and artistic endeavors will have growing implications on education, communication, policy making, media activism, and public perception of science and technology. Abstract : Nano‐/microscale art practices creative activity at small dimensions. It brings together expertise in art and sciences to spur creativity, promote scientific advances, and challenge dominant paradigms. Miniaturized artworks in semiconductors, microfluidics, and nanostructures are reviewed. The perceived limitations of nano‐/microscale artistic practice are discussed and potential future directions are highlighted.